2017
DOI: 10.1186/s12873-017-0135-4
|View full text |Cite
|
Sign up to set email alerts
|

Misuse of emergent healthcare in contemporary Japan

Abstract: BackgroundMedical care is obviously an important public service to ensure the health of a nation; however, medical resources are not always used appropriately. ‘Convenience-store consultations’ and inappropriate ambulance transportation represent instances of such improper use by contemporary Japanese citizens in recent years. This article illustrates two examples of misuse and discusses potential countermeasures by considering factors contributing to these behaviours.Main bodyFrom both public and medical pers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 1 publication
(1 reference statement)
0
7
0
Order By: Relevance
“…Japan adopted a universal healthcare system in 1961 that guarantees patients free access to medical care, 1 and this free access system is proud of Japan. However, the medical staff has been recently exhausted because 1; some patients with mild illness consult doctors in the off-duty hours as so-called convenience-store consultations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Japan adopted a universal healthcare system in 1961 that guarantees patients free access to medical care, 1 and this free access system is proud of Japan. However, the medical staff has been recently exhausted because 1; some patients with mild illness consult doctors in the off-duty hours as so-called convenience-store consultations.…”
Section: Discussionmentioning
confidence: 99%
“…22 A previous report in Japan concluded that we must rely on the spontaneous motivation of patients. 1 The Need for Prediction of Daily Ambulance Transport…”
Section: Problems Of the Health Care System In Japanmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the implication of our finding is that obstetric patients with milder, non-obstetric conditions skip consulting primary or secondary care facilities to access care in the emergency departments of tertiary hospitals. This could result in an increase in the burden on the emergency room staff, making it more difficult for them to care for severely ill patients [11]. Educating the populace on what constitutes urgent obstetric complications, and providing accessible and effective care for medical/surgical issues, especially infectious morbidities occurring in pregnancy, at the secondary facilities are advocated.…”
Section: Discussionmentioning
confidence: 99%
“…Non-urgent use of the emergency department could be for conditions in which a delay of several hours would not lead to an increased likelihood of an adverse outcome [9]. Patients with such conditions, who could have been managed at primary or secondary levels of care, are seen in the emergency rooms of tertiary facilities, most of them by-passing the referral system [10][11]. This scenario has been associated with bogus healthcare spending, unnecessary diagnostic tests and therapies, and poorer patronage of lower tiers of the health care system.…”
Section: Introductionmentioning
confidence: 99%